Associação entre relação cintura/altura e estresse oxidativo em adultos: Um estudo de base populacional. - Chaves, Thamires Ribeiro (2016)
It is important to research about obesity and oxidative stress, as the health complications they entail, being of great interest to elucidate this association by the waist to height (WtHR), a relevant anthropometric indicator of risk of diseases associated with obesity and by oxidative stress markers. The aim of this study was to associate the waist / height with total antioxidant capacity values and malondialdehyde in adults. A cross-sectional population-based study involving 265 individuals from a city in northeastern Brazil. Was collected epidemiological data, and there was the anthropometric and biochemical. Applied to multiple regression using the median of the variables studied. In the total sample, more than half of the participants were overweight and obese. Mean values of 0.51 cm RCA, with the majority of adults (63%) had inadequate RCA (> 0.5). There was a relationship between WtHR and total antioxidant capacity values (t = -4.35; p = 0.000) and Malondialdehyde (t = 2.70, p = 0.007) as well as LDL (t = 2.46, p = 0.015), triglycerides (t = 2.06; p = 0.040) and smoking (t = 3.41; p = 0.001). Abdominal obesity reflected by a slight increase in the RCA has presented itself as an aggravating factor that increases oxidative stress to relate positively with Malondialdehyde values and negatively with Total Antioxidant Capacity values in a population of adults.